Experimental and numerical research of jointed rock mass anisotropy in a three-dimensional stress field (Rudarsko-geološko-naftni zbornik, 2022)
Joints often have a significant influence on material characteristics. The discontinuities’ coalescence mechanism and complex jointed rock mass structure as a composite need to be further explored. In this study, compression and shear tests were carried out on a jointed rock mass. The purpose of the jointed rock mass behaviour study was to determine the deformation-strength dependencies and to determine the parameters for a quantitative assessment of the joints’ influence on mechanical characteristics. The results show that compression strength depends on the materials’ structure, and there is a detailed description of the joints’ orientation influence on stress-strain dependencies during compression experiments. The numerical method used in this study could be used for the modelling of composite materials and their properties.